Checking the Validity and Reliability of the Persian Version of the Resilience Assessment Questionnaire in Patients With Multiple Sclerosis - Fatemeh Ghadbeigi; Fardin Alipour; Gholamreza Ghaedamini Harouni; Zoleikha Arabkari (University of Social Welfare and Rehabilitation Sciences, 2024)
Objective This study aimed to investigate the validity and reliability of the Persian version of the "resilience assessment questionnaire" in patients with multiple sclerosis. Materials & Methods The statistical population of the present study included all multiple sclerosis patients living in Tehran City in 2022. Of them, 250 people were selected through available sampling. The participants completed the questionnaires of Gromis et al. resilience and the hospital anxiety and depression scales. The validity of the questionnaire was investigated using the formal, content, construct, and predictor methods. Also, the reliability of the test was checked through the Cronbach α method and retesting. Data analysis was done using SPSS software, version 26. Results The face validity was confirmed by checking the content and solving the appearance problems. The content validity of the questionnaire was confirmed after correcting the questions. The results of exploratory factor analysis showed that the resilience questionnaire includes 5 components: Emotional and cognitive strategies, physical activity and diet, family and friends support, peer support, and spirituality. Also, the Cronbach α values of these components were 0.88, 0.79, 0.62, 0.76, 0.50, and 0.89, respectively. The eigenvalues of these components explained 47.49% of the variance. There was a significant relationship between the resilience and anxiety/depression questionnaire components. The correlation value between the first and second stages confirmed the retest validity of the resilience questionnaire. Conclusion The Persian version of the "multiple sclerosis resilience" scale is a valid and reliable tool for assessing resilience features in Iranian MS patients, which can be used in policymaking and research studies.